2002
DOI: 10.1111/j.1349-7006.2002.tb01216.x
|View full text |Cite
|
Sign up to set email alerts
|

The Intraductal Carcinoma Component Is a Significant Prognostic Parameter in Patients with Invasive Ductal Carcinoma of the Pancreas

Abstract: We have sometimes encountered invasive ductal carcinomas (IDCs) of the pancreas containing intraductal carcinoma components in the intra-and/or extra-tumor area. The purpose of this study was to investigate whether intraductal carcinoma components would be useful for predicting the outcome of IDC patients. Forty-seven surgically treated IDCs were examined, and all histological tumor sections were stained with Elastica to accurately confirm intraductal carcinoma components. Well-known clinicopathological parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Similar clinicopathological findings have been reported in intraductal papillary–mucinous tumours of the pancreas; such tumours with invasive behaviour are associated a better outcome than invasive ductal carcinoma of the pancreas29–31. Moreover, favourable outcomes for patients with invasive ductal carcinoma of the pancreas32–34 and breast cancer35 have been demonstrated when intraductal carcinoma components are identified. It is likely that some ICCs of the mass‐forming or periductal–infiltrating type with IDPCC might be derived from the intraductal growth‐type tumour and be associated with a favourable outcome.…”
Section: Discussionsupporting
confidence: 70%
“…Similar clinicopathological findings have been reported in intraductal papillary–mucinous tumours of the pancreas; such tumours with invasive behaviour are associated a better outcome than invasive ductal carcinoma of the pancreas29–31. Moreover, favourable outcomes for patients with invasive ductal carcinoma of the pancreas32–34 and breast cancer35 have been demonstrated when intraductal carcinoma components are identified. It is likely that some ICCs of the mass‐forming or periductal–infiltrating type with IDPCC might be derived from the intraductal growth‐type tumour and be associated with a favourable outcome.…”
Section: Discussionsupporting
confidence: 70%
“…It was previously reported that the presence of ICCs in IDCP was a significant good prognostic parameter for patients with IDCP after surgical resection and the survival time of patients with ICC-rich IDCP was almost similar to that of those with ICs from IPMNs (3,13,(22)(23)(24)(25). Furthermore, some studies (24) referred to the morphological similarities of intraductal carcinoma components between IDCP accompanied with ICCs and IPMN and the difficulties in distinguishing between ICC-rich IDCP and ICs from IPMNs (3,4,13,25). This study clearly showed that the frequencies of Dpc4 protein expression of ICC-rich IDCP were significantly higher than that of ICC-poor IDCP in invasive and intraductal carcinoma area and were similar to that in ICs from IPMN.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that among IDCP, about half of them were accompanied by abundant intraductal carcinoma components, corresponding to PanIN-3 of the PanIN classification (containing Ն10% than intraductal carcinoma area among the entire tumorous area; i.e., ICC rich) and were expected to have a more favorable prognosis than the other tumors that were poor in accompanying ICCs (containing Ͻ10% intraductal carcinoma area among the entire tumorous area; i.e., ICC poor; Ref. 3). Fukushima et al (13) also reported that a longer survival was expected for patients whose IDCP had ICCs compared with those without.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerations of the mechanisms of the presence or absence of residual CIS in pCR cases are of interest. Some authors reported that approximately half of PDAC cases were accompanied by a rich intraductal component, whereas the remaining half of PDAC cases were not . In this context, the pCR cases with absence of CIS might originate from tumors that were not originally accompanied by CIS before preoperative treatment, showing complete response in the invasive component to preoperative treatment.…”
Section: Discussionmentioning
confidence: 99%